La crianza infantil en madres de nivel socio-económico bajo - Chan Bazalar, Luis Alberto (2000)
Participants in the research were 200 mothers with a minimum of a one five years old child, coming from urban-marginal zones in the northern cone of city, and who know to read and write although they may not have received a formal education. Research comprised nineteen child-rearing styles used by mothers of a low socioeconomic level. A descriptive designs research was used to identify the child-rearing style in poor families. Results show that most child-rearing practices were deficient, thus creating the need for an individual or group psychological interventions.